Disrupting ACE2 Dimerization Mitigates the Infection by SARS-CoV-2 Pseudovirus - Zhu, Jiaqi; Su, Yue; Tang, Young (Frontiers in Virology, 2022)
The coronavirus disease 2019 pandemic has caused over million death and 500 million reported cases globally. More effective antiviral medications are needed to curb the continued spread of this disease. The infection by SARS-CoV-2 virus is initiated via the interaction between the receptor binding domain (RBD) of the viral glycoprotein Spike (S protein) and the N-term peptidase domain of the angiotensin-converting enzyme 2 (ACE2) expressed on the host cell membrane. ACE2 forms a protein homodimer primarily through its ferredoxin-like fold domain (a.k.a., Neck-domain). We investigated whether the dimerization of ACE2 receptor plays a role in SARS-CoV-2 virus infection. We report here that the ACE2 receptor dimerization enhances the recognition of SARS-CoV-2 S protein. A 43-amino-acid peptide based on the N-term of Neck-domain could block the ACE2 dimerization and hence the interaction between RBD and ACE2 and mitigate the SARS-CoV-2 S protein pseudotyped virus/host cell interaction. Our study illustrated a new route to develop potential therapeutics for the prevention and treatment of SARS-CoV-2 viral infection.